Digital evolution of ESG 3.0 : advancing corporate governance and sustainability - Ali, Muhammad; Leong, Choi-Meng; Fung, Chorng Yuan; Puah, Chin-Hong; Raza, Syed Ali; Lau, Evan (Emerald Publishing Limited, 2026)
Environmental, Social and Governance (ESG) principles are essential for organizations to embrace, but what impact does digital technology have on ESG and corporate social responsibility? The research presented in the book examines how this intersection is transforming corporate governance practices and sustainability programs, with an in-depth exploration of the digital tools and technologies that are contributing to beneficial impacts on ESG performance, accountability, and stakeholder engagement. The chapters offer a comprehensive and detailed analysis of the latest developments, difficulties, and possibilities in digital ESG management. They provide practical and effective approaches for organizations to successfully navigate the intricate aspects of sustainability in the digital era. Readers acquire useful insights into the implementation of digital governance frameworks and the utilization of technology to improve ESG performance and stakeholder communication. It offers readers useful insights and practical approaches to promote positive transformations in corporate governance and sustainability.